Answer:
the right answer is:
- (A)
![2+(1)/(2)a](https://img.qammunity.org/2022/formulas/mathematics/high-school/k2tiggmwgleh2vmhe0qmw2p53l55ksoyga.png)
Explanation:
You take the equations that the exercise give you:
- x + y = 4
- x - y = a
Now you clear the "y" variable in any equation you want, in this case, I'm gonna use the second equation:
3. y = x - a
And now, you'll replace this third equation in the equation you didn't take (the first in this case).
- x + y = 4
- x + (x - a) = 4
- x + x - a = 4
Add the x variables:
- 2x - a = 4
- 2x = 4 + a
- x = (4 + a) / 2
That's the answer of the exercise, but you can represent this in this form:
- x = (4 + a) / 2 ↔
![x = (4)/(2) + (1)/(2) a](https://img.qammunity.org/2022/formulas/mathematics/high-school/un0h4rox7lapxnc81vc0jkcazj1ihtok4g.png)
- x = (4 + a) / 2 ↔
![x = 2+ (1)/(2) a](https://img.qammunity.org/2022/formulas/mathematics/high-school/c2n14o6idl696zepvckmz319yiw7fv25w9.png)
By this reason, the right answer is
.